Understanding the sources and capabilities which MASTEK requires to enter the financial services IT application software industry.What are the likely challenges and benefits to MASTEK - Ranjan, Ashish (2011)
The role of Diversification is very important in increasing revenue and profit of an organisation. How can an IT firm gain advantage from this fact? Can MASTEK further diversify into UK capital market? How it can gain mileage from its financial service operations in Asia-Pacific. How can knowledge relatedness lead to successful diversification of an IT firm?